2004
DOI: 10.1596/1813-9450-3293
|View full text |Cite
|
Sign up to set email alerts
|

On the Conservation of Distance in International Trade

Abstract: The volume of world trade has grown more than twice as fast as real world income since 1980. Surprisingly, the effect of distance on trade has increased during this period. It could be that countries are trading greater volumes of goods that are highly sensitive to distance. An alternative explanation is that distance has become more import for a significant share of goods. Using highly disaggregated bilateral trade data, we find that adjustment in the composition of trade has not influenced the way in which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
99
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 22 publications
10
99
0
1
Order By: Relevance
“…We provide these GE effect estimates for all (bilateral) trade flows of each of our 40 countries and the ROW aggregate, the trade flows 41 Coe et al (2007) found evidence of declining distance elasticities by employing non-linear estimation (including PQML), although the declines ended between 1990 and 2000, but could not find declining distance elasticities using OLS. Berthelon and Freund (2008) found rising distance elasticities since 1985 using OLS. Larch etal (2015) found a declining distance effect using non-linear estimators, but not using OLS.…”
Section: General Equilibrium Comparative Staticsmentioning
confidence: 94%
See 1 more Smart Citation
“…We provide these GE effect estimates for all (bilateral) trade flows of each of our 40 countries and the ROW aggregate, the trade flows 41 Coe et al (2007) found evidence of declining distance elasticities by employing non-linear estimation (including PQML), although the declines ended between 1990 and 2000, but could not find declining distance elasticities using OLS. Berthelon and Freund (2008) found rising distance elasticities since 1985 using OLS. Larch etal (2015) found a declining distance effect using non-linear estimators, but not using OLS.…”
Section: General Equilibrium Comparative Staticsmentioning
confidence: 94%
“…6 Unfortunately, there is little systematic evidence of observed declines in bilateral fixed and variable export costs. A few studies have explored the issue of declining information technology (IT) costs, cf., Freund and Weinhold (2004), Tang (2006), and Berthelon and Freund (2008). However, all these studies include time-varying multilateral, not bilateral, indexes of IT factors.…”
Section: Introductionmentioning
confidence: 99%
“…For Australia the only substitution option is between sea and air transport. 5 Harrigan and Deng (2008), Berthelon and Freund (2008), Egger (2008), Moreira et al (2008) and Hummels and Schaur (2009) contribute to this literature and provide references to other work. 6 Although bulk accounts for some commodity characteristics, we are unable to take account of other characteristics such as perishability or fashion which influence the choice of air or sea transport.…”
Section: Introductionmentioning
confidence: 94%
“…The adjusted costs, however, reveal the higher costs of air transport once weight/value is taken into account. The adjusted values indicate a larger percentage Berthelon and Freund (2008) conclude from their disaggregated gravity model analysis that the importance of distance over time is related to the substitutability of goods, i.e. distance is more relevant to the cost of trading differentiated manufactured goods than to trade in homogeneous primary products.…”
Section: Datamentioning
confidence: 99%
“…differences in legal infrastructure, enforcement of the law, accessibility to the regulatory system or corruption environment) result in only partial information being available on the potential for trade and the uncertainty involved. These factors constitute additional costs of trade that are unobserved and informal, particularly with regard to the costs of gathering relevant trade information and of signing contracts and enforcing them (see Berthelon andFreund 2004 andHofstede 2001).…”
Section: Introductionmentioning
confidence: 99%